Enhanced Energy Storage Properties of Polypropylene/Glycidyl Methacrylate Grafted Polypropylene/Nano-ZrO2 Ternary System - Chong Zhang; Zhaoliang Xing; Xin Chen; Shaowei Guo; Hongbo Liu; Lu Cheng; Wenfeng Liu (Energies, 2023)
Extensive research has focused on enhancing the energy storage density of polypropylene (PP) to meet the demands of high-power and compact electronic devices and electrical systems. However, there is a lack of studies addressing the delicate balance between energy storage density and dielectric loss. Dielectric loss can lead to excessive heat generation, posing a threat to the operation of energy storage capacitors. In this study, PP grafted with glycidyl methacrylate (GMA) was used as a compatibilizer and incorporated into a PP/nano ZrO2 blend to form a ternary system of PP/nano ZrO2/PP grafted GMA. A comparative study was conducted to analyze the effects of GMA grafting and individual doping of nano ZrO2 on the dielectric performance of PP. The results demonstrate that the ternary system not only ensures a high breakdown voltage (382.29 MV/m) but also possesses a high dielectric constant (2.67), thereby achieving an energy storage density of 1.7275 J/cm3 while maintaining low dielectric loss. Furthermore, grafting GMA introduces a significant number of deep traps, a phenomenon substantiated by the results of thermal stimulated depolarization current tests and molecular simulation calculations. However, the ternary system partially avoids the introduction of excessive deep traps associated with GMA grafting. This ternary system exhibits excellent energy storage performance, ease of fabrication, and stability, thereby enriching the research on polymer-based high-energy density dielectric materials.